The twentieth-century English university and its exclusions: literature and the politics of expanding higher education - Lu, M (2020)
This thesis, situated at the intersection of literary scholarship, intellectual and social history, and critical university studies, explores the richly heterogeneous, and largely overlooked, body of responses by a number of major literary writers to the mass expansion of higher education during the ‘long twentieth century.’ The discussions trace how literary writers problematised the dominant cultural narratives about the extension of access to English higher education and responded to the ideological tensions between democratic and emerging meritocratic principles as they played out in educational reforms. I examine how their works bring to light the rigid hierarchisation of universities in the English system and the concerning correlations between this hierarchy and the reproduction of wider social inequalities. What was, initially, understood as a problem mostly of class has been rewritten over and over again as a problem, also, of gender, of race, of sexual orientation, and of ableist biases. Chapters 1-5 shed light on those aspects of the writings of E. M. Forster, D. H. Lawrence, Virginia Woolf, Evelyn Waugh, and W. H. Auden that evidence significant, and sometimes surprising, investments in the issues surrounding under-representation, underachievement, and maladjustment of certain groups of students. A final chapter considers educational ‘access’ from a present-day vantage point by turning to Zadie Smith’s university narratives, which deepen our appreciation of the prescience of earlier writers who anticipated some of the controversies that would beset the contemporary ‘neoliberal’ and ‘meritocratic’ university. This thesis, in short, demonstrates how longstanding dissatisfactions with the universities’ manifold forms of exclusivity have been; how idealism in this area keeps getting abraded by socioeconomic and political realities; and the diverse range of ways in which modern literary writers have articulated and finessed their criticisms of institutional entrenchments of intersectional disadvantage.